KRITIK PANDANGAN MAHMUD ABU RAYYAH TERHADAP TADWIN HADIS - Munandar Munandar (SHAHIH (Jurnal Ilmu Kewahyuan), 2019)
"Mahmud Abu Rayyah's criticism is divided into several basic things in the study of Hadith; The first, regarding the codification of the Hadith. The second, the Isrāīliat narrations. The third, the prohibition of writing the Hadith. The fourth, Abu Rayyah's criticism of the tadwin hadith of friends is also a concern in his book Adhwa ‘ala as Sunnah al Muhammadiyyah. Many writers are interested in examining the thoughts of Mahmud Abu Rayyah in the study of critics of the sanad of the Hadith that are related to the thoughts of Abu Rayyah.”